Back Cover: New Polydentate Trimethylsilyl Chalcogenide Reagents for the Assembly of Polyferrocenyl Architectures (Chem. Eur. J. 23/2014). Issue 23 (2nd June 2014) - Fard, Mahmood Azizpoor; Khalili Najafabadi, Bahareh; Hesari, Mahdi; Workentin, Mark S.; Corrigan, John F.
<x xml:space="preserve">Abstract</x> Polyferrocenyl architectures are prepared from a series of new poly(trimethylsilylchalcogen) reagents and ferrocenoyl chloride. As described in the Full Paper by J. F. Corrigan et al. on p. 7037 ff., the assemblies are formed via thioester or selenoester linkages, tethering the ferrocenyl fragments to a central ring.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>